Clinical Effectiveness of SARS-CoV-2 Booster Vaccine Against Omicron Infection in Residents and Staff of Long-term Care Facilities: A Prospective Cohort Study (VIVALDI). (29th December 2022) - Stirrup, Oliver; Shrotri, Madhumita; Adams, Natalie L; Krutikov, Maria; Nacer-Laidi, Hadjer; Azmi, Borscha; Palmer, Tom; Fuller, Christopher; Irwin-Singer, Aidan; Baynton, Verity; Tut, Gokhan; Moss, Paul; et al.
Abstract: Background: Successive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants have caused severe disease in long-term care facility (LTCF) residents. Primary vaccination provides strong short-term protection, but data are limited on duration of protection following booster vaccines, particularly against the Omicron variant. We investigated the effectiveness of booster vaccination against infections, hospitalizations, and deaths among LTCF residents and staff in England. Methods: We included residents and staff of LTCFs within the VIVALDI study (ISRCTN 14447421) who underwent routine, asymptomatic testing (December 12, 2021–March 31, 2022). Cox regression was used to estimate relative hazards of SARS-CoV-2 infection, and associated hospitalization and death at 0–13, 14–48, 49–83, 84–111, 112–139, and 140+ days after dose 3 of SARS-CoV-2 vaccination compared with 2 doses (after 84+ days), stratified by previous SARS-CoV-2 infection and adjusting for age, sex, LTCF capacity, and local SARS-CoV-2 incidence. Results: A total of 14 175 residents and 19 793 staff were included. In residents without prior SARS-CoV-2 infection, infection risk was reduced 0–111 days after the first booster, but no protection was apparent after 112 days. Additional protection following booster vaccination waned but was still present at 140+ days for COVID-associated hospitalization (adjusted hazard ratio [aHR], 0.20; 95% CI, 0.06–0.63) and death (aHR, 0.50; 95% CI, 0.20–1.27). Most residents (64.4%) had received primary course vaccine of AstraZeneca, but this did not impact pre- or postbooster risk. Staff showed a similar pattern of waning booster effectiveness against infection, with few hospitalizations and no deaths. Conclusions: Our findings suggest that booster vaccination provided sustained protection against severe outcomes following infection with the Omicron variant, but no protection against infection from 4 months onwards. Ongoing surveillance for SARS-CoV-2 in LTCFs is crucial.